Gender Differences in Severity and Correlates of Depression Symptoms in People Living with HIV in Ontario, Canada. (January 2016) - Aljassem, Kinda; Raboud, Janet M.; Hart, Trevor A.; Benoit, Anita; Su, DeSheng; Margolese, Shari L.; Rourke, Sean B.; Rueda, Sergio; Burchell, Ann; Cairney, John; Shuper, Paul; Loutfy, Mona R.; et al.
This study investigates the differences in severity and correlates of depression symptoms among 1069 men and 267 women living with HIV in Ontario, Canada, who completed the 20-item Center for Epidemiologic Studies Depression Scale (CES-D). Women had higher CES-D scores than that of men (median [interquartile range]: 13 [5-26] versus 9 [3-20], P = .0004). More women had total CES-D scores >15 (mild-moderate depression; 44% versus 33%, P = .002) and >21 (severe depression; 31% versus 23%, P = .003). Unlike men, at age 40, women's scores increased yearly (0.4 per increased year, P = .005). The distribution of scores differed by gender: There was no difference in the 10th percentile of depression scores, 0 (95% confidence interval [CI]: 1.0-1.0) but the 75th percentile of depression scores for women was 6 (95% CI: 2.0-10.0) points higher than that of men. Important gender differences exist in depression symptoms and in correlates of symptoms in people living with HIV.